Editorial: Neuroanatomy of cognition - Bendersky, Mariana (2024)
Neuroanatomy of cognition is a complex and evolving field of study that explores the structural and functional bases of cognitive processes. Research in this area delves into the neural structures and pathways involved in cognitive domains, such as attention, memory, language, and decision-making. Studying the neuroanatomical underpinnings of cognition is crucial to understand normal brain function and addressing neurological disorders affecting cognition. This knowledge can help to develop more effective treatments and interventions for various cognitive conditions.